Money and households in a capitalist economy - Todorova, Zdravka (Edward Elgar, 2009)
Post Keynesian analyses of monetary production have not given much attention to households as institutions, while a good deal of the literature in feminist economics discusses households in a strictly microeconomic context, with little consideration of monetary phenomena. This book, a unique study of the capitalist economy, utilizes a distinctive combination of Post Keynesian, institutional, and gender analysis to examine household economics in capitalist society in order to flesh out the gaps in each.
10.4337/9781848449466
Keywords: Mikroökonomie; Haushalt; Neokeynesianismus; Geschlechterforschung